Effect of indium content on X- ray diffraction and optical constants of InxSe1-x thin films - Hasan, Bushra A. (Iraqi Journal of Physics, 2019)
Alloys of InxSe1-x were prepared by quenching technique withdifferent In content (x=10, 20, 30, and 40). Thin films of these alloyswere prepared using thermal evaporation technique under vacuum of10-5 mbar on glass, at room temperature R.T with differentthicknesses (t=300, 500 and 700 nm). The X–ray diffractionmeasurement for bulk InxSe1-x showed that all alloys havepolycrystalline structures and the peaks for x=10 identical with Se,while for x=20, 30 and 40 were identical with the Se and InSestandard peaks. The diffraction patterns of InxSe1-x thin film showthat with low In content (x=10, and 20) samples have semicrystalline structure, The increase of indium content to x=30decreases degree of crystallinity and further increase of indiumcontent to x=40 leads to convert structure to amorphous. Increase ofthickness from 300 to 700nm increases degree of crystallinity for allindium content. Transmittance measurements were used to calculaterefractive index n and the extinction coefficient k using Swanepole’smethod. The optical constants such as refractive index (n), extinctioncoefficient (k) and dielectric constant (εr, εi) increases for low indiumcontent samples and decreases for high indium content samples,while increase of thickness increases optical constants for all xvalues. The oscillator energy E0, dispersion energy Ed, and otherparameters have been determined by Wemple - DiDomenico singleoscillator approach.